Celluloid revolt : German screen cultures and the long 1968 - Gerhardt, Christina; Abel, Marco (Rochester, New York : Camden House, 2019)
"The epoch-making revolutionary period universally known in Germany as '68 can be argued to have predated that year and to have extended well into the 1970s. It continues to affect German society and culture to this day. Yet while scholars have written extensively about 1968 and the cinema of other countries, relatively little sustained scholarly attention has thus far been paid to 1968 and West German, East German, and Austrian cinemas. Now, five decades later, Celluloid Revolt sets out to redress that situation, generating new insights into what constituted German cinema around 1968 and beyond. Contributors engage a range of cinemas, spanning experimental and avant-garde cinema, installations and exhibits; short films, animated films, and crime films; collectively produced cinemas, feminist films, and Arbeiterfilme (workers' films); as well as their relationship to cinemas of other countries, such as French cinéma vérité and US direct cinema"--
Introduction : German screen cultures and the long 1968 / Christina Gerhardt and Marco Abel -- Peter Zadek's Ich bin ein Elefant, Madame : discussing "1968" by means of "1968 thinking" / Michael Dobstadt -- "Break the power of the manipulators" : film and the West German 1968 / Timothy Scott Brown -- Ideological rupture in the dffb : an analysis of Hans-Rüdiger Minow's Berlin, 2. Juni / Priscilla Layne -- Helke Sander's dffb films and West Germany's feminist movement / Christina Gerhardt -- Film feminisms in West German cinema : a public sphere for feminist politics / Madeleine Bernstorff -- A laboratory for political film : the formative years of the German film and television academy and participatory filmmaking from workerism to feminism / Fabian Tietke -- West Germany's "workers' films" : a cinema in the service of television? / Thomas Elsaesser -- Guns, girls, and gynecologists : West German exploitation cinema and the St. Pauli film wave in the late 1960s / Lisa Haegele -- Mediation, expansion, event : reframing the Austrian filmmakers cooperative / Andrew Stefan Weiner -- Prague displaced : political tourism in the East German blockbuster Heisser Sommer / Ian Thomas Fleishman -- Animating the socialist personality : DEFA fairy tale trickfilme in the shadow of 1968 / Sean Eedy -- Allegories of resistance : the legacy of 1968 in GDR visual cultures / Patricia Anne Simpson -- "You say you want a revolution" : East German film at the crossroads between the cinemas / Evelyn Preuss -- Cruel optimism, post-68 nostalgia, and the limits of political activism in Helma Sanders-Brahms's Unter dem Pflaster ist der Strand / Ervin Malakaj -- Revolting formats : Hellmuth Costard's Der kleine Godard : an das Kuratorium junger Deutscher film / Kalani Michell -- An interview with Harun Farocki : "Holger thought about aesthetics and politics together" / Tilman Baumgärtel -- An interview with Birgit Hein : "Art communicates knowledge that cannot be expressed in any other information system" / Randall Halle -- An interview with Klaus Lemke: "Being smart does not make good films" / Marco Abel.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Motion pictures -- Germany (West) -- History; Motion pictures -- Germany (East) -- History; Motion pictures -- Austria -- History -- 20th century; Cinéma -- Allemagne (Ouest) -- Histoire; Cinéma -- Allemagne (Est) -- Histoire; Cinéma -- Autriche -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference; PERFORMING ARTS / Film & Video / History & Criticism; Motion pictures; Austria; Germany (East); Germany (West); 1900-1999; 1968.; French cinéma vérité.; German cinema; US direct cinema; cinema; cultural and political happenings; cultural impact; revolution; screen cultures; History